Perceived Ease of Use, Trust and Risk toward Attitude and Intention in Shopping for Online Fashion Products In Indonesia - Suleman, Dede; Ali, Hapzi; Nusraningrum, Dewi; Ali, Mochammad Mukti (Archives of Business Research, 2019)
This study aims to analyze the partial influence of perceived ease, trust and risk on the attitudes and intentions of consumers shopping online. This study uses purposive sampling in the survey method to produce a sample of 74 respondents from the city of Jakarta in Indonesia. The findings of this study indicate that there is a perception of convenience does not affect the attitudes and intentions of consumers. While trust and risk factors are factors that significantly influence the attitudes and intentions of consumers to shop online. Shopping attitudes are influenced by constructs of perceived ease of use, risk and trust, because shopping attention is influenced by the construct of shopping attitudes, perceptions of ease of use, risk, and trust. The results of this study function for online shop entrepreneurs to develop effective strategies to make consumers believe and minimize risks when shopping online so that consumers have a positive attitude and then the intention to shop online.